Analytical Solution of Fractional BSM Differential Equation for ML-Payoff Function Using GDTM - S J Ghevariya (International Journal of Mathematics And its Applications, 2019)
This paper contributes to the analytical solution of fractional Black-Scholes-Merton (BSM) differential equation to obtain European option pricing formula for Modified Log-payoff (ML-Payoff) function, $\max\{S\ln\big(\frac{S}{K}\big),0\}$ using Generalized Differential Transform Method (GDTM). It turns out that the BSM formula for ML-Payoff function using GDTM is quite close to the closed form solution of BSM model for ML-Payoff function.